Tokyo 2020 or 2021? The Perceived Impact of the COVID-19 Pandemic on Portuguese Olympic and Paralympic Athletes - Inês Miguel Santos Silva (2021)
For the first time in history, the Olympic Games were postponed due to the dissemination of the new coronavirus, causing a physical and psychological impact on all involved, especially athletes. Within this context, it is essential to understand how Olympic and Paralympic athletes perceived and are dealt with this crisis. The current dissertation aimed to explore the experience of Portuguese Olympic and Paralympic athletes, through their perceptions and emotions (study I), as well as the coping strategies used to manage the impact of the lockdown and of the postponement of the Olympic Games 2020 (study II). Using a qualitative methodology, data were collected through semi-structured online interviews with 15 athletes (M = 29,9 ± 5,5 years) from both sexes (nmale = 9), including 13 Olympic athletes and two Paralympic athletes of various sports. A content analysis was performed in each study. Overall, our studies revealed that participants had multiple perceptions regarding the Olympic Games, their social and personal life, their physical and health conditions, and sports related areas, both on training and competition. Emotions referred comprise negative-toned and positive-toned. The negative-toned emotions were more expressive in the results, especially anxiety. The most used word to describe this event was adaptability. Athletes revealed to have used more coping strategies included in the appraisal-focused and approach coping styles, whereas the avoidance coping style was the least used. Adjusting to the constraints, looking for the positive side of negative events, negotiation, and acceptance revealed to be the most used coping strategies within this sample. The results reassure the individual, dynamic, and complex nature of athletes' experience. This one-time event created the opportunity to study the situation from the athletes' points of view. Findings can now be used to help other athletes and sports agents to prevent and deal with other stressful situations. These results highlight the importance of developing interventions directed at promoting coping strategies and social and personal competences in all athletes, regardless of their level of competition, as well as programmes that create awareness within other sports agents.